AlN/GaN/AlGaN-on-Si HEMT achieving 1.3 W/mm at 5 v for 5G FR2 handsets - Li, Hanchao (2025)
This Letter reports a double heterostructure (DH) AlN/GaN/AlGaN-on-Si HEMT, which has been proposed, for low voltage (LV, ≤5 V) RF operation. The proposed transistor shows excellent DC (Idmax = 1.9 A/mm, gmmax = 0.66 S/mm) and RF small-signal characteristics (fT/fmax = 145/195 GHz). Continuous-wave (CW) load-pull measurements at 30 GHz yield Psat of 0.6 (1.3) W/mm at Vds of 3.5 (5) V, and peak power-added efficiency (PAE) of 43% (42%). To the best of the authors' knowledge, the Psat values are the highest reported for LV GaN-on-Si HEMTs in 5G FR2, despite the use of conventional alloyed contacts and a gate length (Lg) of 120 nm. Furthermore, among published LV GaN-on-Si HEMTs, the proposed transistor achieves a desired combination of saturation velocity (Vsat) and knee voltage (Vknee), which are critical factors for LV power amplification. The results reflect the promising potential of the proposed heterostructure to achieve high transmit power in 5G FR2 handsets..